Identification of the major metabolites of (R)‐salbutamol in human urine, plasma and feces using ultra high performance liquid chromatography coupled with quadrupole time‐of‐flight mass spectrometry. Issue 20 (21st August 2019) - Ye, Fengying; Liu, Shan; Yang, Yang; Zhao, Ting; Li, Shuang; Zhou, Ting; Tan, Wen
Abstract: (R)‐Salbutamol is a selective β2‐adrenoreceptor agonist, which produces a short‐acting bronchodilator effect and is widely used for the treatment of respiratory diseases in humans. Drug metabolism and identification of the metabolites play an essential role in the evaluation of the overall efficacy and safety of the drugs in clinical practices. There are few reports on the identification of major metabolites of (R)‐salbutamol in humans, and the number of identified metabolites is very limited. In this research, a method of ultra‐high performance liquid chromatography coupled with quadrupole time‐of‐flight mass spectrometry was developed for the discovery and identification of (R)‐salbutamol and its major metabolites in human biological samples. Totally, twelve metabolites of (R)‐salbutamol were found and identified and all the metabolites could be found in urine, one metabolite in plasma and two metabolites in feces. Among all the metabolites, eight metabolites have never been reported before. The results indicated that (R)‐salbutamol was mainly metabolized through isomerization, oxidation, reduction, glucuronidation, and sulfation pathways in vivo. The possible metabolic pathways of (R)‐salbutamol were subsequently presented in this study, which contribute to a better understanding of the metabolism of (R)‐salbutamol in humans.